2023
DOI: 10.1136/thorax-2023-219989
|View full text |Cite
|
Sign up to set email alerts
|

Persistent alveolar inflammatory response in critically ill patients with COVID-19 is associated with mortality

Abstract: IntroductionPatients with COVID-19-related acute respiratory distress syndrome (ARDS) show limited systemic hyperinflammation, but immunomodulatory treatments are effective. Little is known about the inflammatory response in the lungs and if this could be targeted using high-dose steroids (HDS). We aimed to characterise the alveolar immune response in patients with COVID-19-related ARDS, to determine its association with mortality, and to explore the association between HDS treatment and the alveolar immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Steroids were associated with decreased BAL neutrophils in a case series of 12 patients with COVID-19 ARDS who required ECMO 39 . In patients with non-resolving ARDS, steroid treatment was associated with decreased BAL concentrations of the neutrophil chemoattractants CXCL1 and CCL20 40 . Two observational studies have described the effects of dexamethasone on gene expression in patients with COVID-19 ARDS.…”
Section: Discussionmentioning
confidence: 95%
“…Steroids were associated with decreased BAL neutrophils in a case series of 12 patients with COVID-19 ARDS who required ECMO 39 . In patients with non-resolving ARDS, steroid treatment was associated with decreased BAL concentrations of the neutrophil chemoattractants CXCL1 and CCL20 40 . Two observational studies have described the effects of dexamethasone on gene expression in patients with COVID-19 ARDS.…”
Section: Discussionmentioning
confidence: 95%
“…It also recruits Th17 cells and regulatory T cells to inflammatory sites since CCR6 is present on these cell types. Patients with COVID-19 were found to have elevated levels of CCL20 in both bronchoalveolar lavage (BAL) fluid and plasma samples 46 . Pulmonary arterial hypertension in individuals with SSc is associated with elevated serum CCL20 levels 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Joint modeling is a flexible approach that can mitigate some of the effects of informative censoring 28 . The latter is particularly relevant for translational studies in the ICU because patients who experienced early mortality or those who improved quickly and were discharged from the ICU could not contribute later follow-up samples 46 . Our joint models revealed that baseline features in the lung compartment (Shannon index and anaerobe or pathogen abundance) were predictive of survival, whereas their longitudinal changes were not, except for marginal effects of anaerobe abundance.…”
Section: Discussionmentioning
confidence: 99%